2022
DOI: 10.1080/21645698.2022.2025725
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of genetically modified insect-resistant maize and non-transgenic maize revealed changes in soil metabolomes but not in rhizosphere bacterial community

Abstract: The deliberate introduction of the beneficial gene in crop plants through transgenic technology can provide enormous agricultural and economic benefits. However, the impact of commercialization of these crops on the ecosystem particularly on belowground soil biodiversity is still uncertain. Here, we examined and compared the effects of a non-transgenic maize cultivar and an insect-resistant transgenic maize cultivar genetically engineered with cry1Ah gene from Bacillus thurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…The field residue of Cry3Bb transgenic corn MON863 has no impact on changes in bacterial communities in soil, but does have a small impact on fungal communities, mainly due to changes in environmental factors, which are not related to differences in the variety of corn [ 39 ]. In other studies, researchers have found that the planting of Cry1Ah transgenic maize HGK60 produces no significant differences in the composition and diversity of bacterial communities compared to controls at the same growth stage, but differences have been identified among different growth periods [ 30 , 47 ]. In the current study, a one-year field trial was adopted to investigate the impact of the transgenic maize 2A-7 on the composition and diversity of microbial communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The field residue of Cry3Bb transgenic corn MON863 has no impact on changes in bacterial communities in soil, but does have a small impact on fungal communities, mainly due to changes in environmental factors, which are not related to differences in the variety of corn [ 39 ]. In other studies, researchers have found that the planting of Cry1Ah transgenic maize HGK60 produces no significant differences in the composition and diversity of bacterial communities compared to controls at the same growth stage, but differences have been identified among different growth periods [ 30 , 47 ]. In the current study, a one-year field trial was adopted to investigate the impact of the transgenic maize 2A-7 on the composition and diversity of microbial communities.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing analysis of the hypervariable regions can easily distinguish different bacterial species. Therefore, 16S rDNA sequencing is widely used to evaluate microbial phylogeny, classification, and diversity [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…A method for introducing the BADH gene into plants with a defect in the glycine betaine pathway that reduces their salt–stress resistance, such as Arabidopsis, Ammopiptanthus nanus, maize, potato, Persian walnut, wheat, etc., has been proposed [ 34 , 35 , 36 , 37 , 38 , 39 ]. With the continuous development of transgenic plant varieties, monitoring the environment after their large-scale cultivation has received increasing attention in the past 20 years, especially insect-resistant or herbicide-tolerant crops [ 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. As a result, the potential non-target impacts caused by transgenic plants can form a critical component of risk assessments in environmental management.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Chen et al [108] did not investigate a limited number of elements but rather performed a comprehensive profiling of the soil metabolomes of Bt maize and a non-transgenic variety. Soil metabolomics profiling generated a total of 1730 compounds that differed at each of the six growth stages.…”
Section: Factors Influencing the Interaction Of Transgenic Plants Wit...mentioning
confidence: 99%